Evaluasi Proses Pemindahan Bangunan Vernakular Jawa pada Pawon Garden di Parung Kabupaten Bogor - Anassya Calistha Dewani (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Pawon Garden is a complex of Javanese vernacular buildings whose dominant buildings are Javanese vernacular buildings that were moved from their original place to a plot of land in Parung District, Bogor. This study aims to determine the process of moving Javanese vernacular buildings that occur in Pawon Garden Parung in a narrative way. The research was conducted with a qualitative descriptive approach. The results showed that the translocation process of Javanese vernacular buildings, starting from technical specifications, elements, and materials, was discussed in 3 stages: the disassembly process; transfer process; and the reconstruction process. There are several changes to the building that occurred as a form of adjustment of the building to its new environment and functions. The changes made, reduce the level of authenticity of the building, however, most of the elements and structures in the translocated Javanese vernacular buildings are still the original components of the building that was built.